STUDY OF DRAINAGE PLAN FOR PAJANG WAREHOUSING AREA TANGERANG CITY (International Journal of Psychosocial Rehabilitation, 2020)
In the area of Pajang, Tangerang City, south of Soekarno-Hatta Airport, a warehousing center with an area of ± 6 ha will be built. Existing land is vacant land that has not been equipped with a drainage system. Based on the technical principles and policies of the local government related to the urban water system and flood control, it is necessary to find the right solution to minimize the impact that will occur due to the construction of these facilities without disrupting the existing water system. Therefore, a technical study is needed in the form of a Study of Drainage Plan for Pajang Warehousing Area Tangerang City. Based on the analysis that has been done, the planned drainage channel network and the creation of a retention pond in the Pajang Warehouse can minimize the impact of flooding both in the warehousing and non-warehousing areas.